Factors Affecting the Consumption of Plant Nutrients in Arid and Semi-Arid Districts of Rajasthan - Diwakar, G D; Sehara, D B.S (Annals of Arid Zone, 2016)
The study reveals that area under tenancy and rural literacy extended maximum influence in semi-arid districts while rural literacy did not show any significant effect on the use of plant nutrients in arid districts of Rajasthan. Area under tenancy showed negative effect on the use of nitrogenous and potassic nutrients in arid districts but in case of phosphatic nutrients its effect was positive and significant. On the other hand, annual rainfall influenced the use of nitrogenous and potassic nutrients significantly in arid districts. Gross cropped irrigated area was observed significantly affecting the use of all the nutrients separately and in combination of in arid districts while the same did not influence the use of any of the nutrients significantly in semi-arid districts. Average size of holding showed positive effect in arid districts but it influenced negatively the use of nutrients in semi-arid districts of Rajasthan.